Comparative transcriptomics as a tool for the identification of root branching genes in maize. Issue 9 (14th August 2013) - Jansen, Leentje; Hollunder, Jens; Roberts, Ianto; Forestan, Cristian; Fonteyne, Philippe; Van, Charlotte; Zhen, Rui‐Guang; McKersie, Bryan; Parizot, Boris; Beeckman, Tom
Summary The root system is fundamental for plant development, is crucial for overall plant growth and is recently being recognized as the key for future crop productivity improvement. A major determinant of root system architecture is the initiation of lateral roots. While knowledge of the genetic and molecular mechanisms regulating lateral root initiation has mainly been achieved in the dicotyledonous plant Arabidopsis thaliana, only scarce data are available for major crop species, generally monocotyledonous plants. The existence of both similarities and differences at the morphological and anatomical level between plant species from both clades raises the question whether regulation of lateral root initiation may or may not be conserved through evolution. Here, we performed a targeted genome‐wide transcriptome analysis during lateral root initiation both in primary and in adventitious roots of Zea mays and found evidence for the existence of common transcriptional regulation. Further, based on a comparative analysis with Arabidopsis transcriptome data, a core of genes putatively conserved across angiosperms could be identified. Therefore, it is plausible that common regulatory mechanisms for lateral root initiation are at play in maize and Arabidopsis, a finding that might encourage the extrapolation of knowledge obtained in Arabidopsis to crop species at the level of root system architecture.